Greenspace Governance: Statutory Solutions from Scotland?. (6th December 2017) - Dickinson, Jill; Marson, James
Abstract: The environmental, social, and economic benefits provided by greenspace are well documented, and the closure of other types of Third Place has popularized them further. Yet, public sector funding cuts have necessitated local authorities prioritizing other facilities that they are statutorily obliged to provide, resulting in a facilities-hierarchy that leaves financially neglected greenspaces facing a vicious circle of decline. The Big Society agenda has seen local authorities increasingly rely on the voluntary sector to help plug the funding gap, yet there are concerns that such groups are not immune from the effects of austerity themselves, which limit their panacean abilities. In exploring whether statute could provide any answers to these greenspace governance challenges, this article considers the lessons to be learned from the approach adopted in Scotland, underpinned by the Land Reform (Scotland) Act 2003 ('the 2003 Act'). In particular, the 2003 Act establishes public rights of access over most greenspace, a local authority duty to uphold these rights and local authority powers to take remedial action. While there have been some issues in implementation, this article explores the potential for adopting a similar model in England and Wales to help secure the future of its greenspace infrastructure.